Program closures: What happens to faculty left behind? - Lilian H. Hill; E. Paulette Isaac-Savage (Adult Education Research Conference, 2021)
This autoethonographic study documents the stories of two adult education faculty members’ experiences when their academic programs were closed. In both cases, they each became programs of one after colleagues retired or left for other reasons. Despite their isolation as the only faculty members with adult education credentials, both continue to conduct research, teach, mentor students and colleagues, and remain engaged with the field of adult education.
Keywords: program closure; autoethnography; institutional assessment